KEPUASAN KONSUMEN RUMAH TANGGA TERHADAP BERAS PADI ASAL LAMPUNG SELATAN (BERAS “PALAS”) DI KABUPATEN LAMPUNG SELATAN - Dela Fitriana; Teguh Endaryanto; Rabiatul Adawiyah (Lampung University, 2020)
This research aimed to find out consumption pattern and level of satisfaction of household consumers on “Palas” rice. The research was done in South Lampung with a survey method. The data was collected in Mei 2018. The technique used for sampling was nonprobability sampling with 40 respondents. The analysis methods used were descriptive analysis, Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The research showed that the household consumers of “Palas” rice consumed 9.12 kg per month. They consume “Palas” rice because the quality of “Palas” rice is quite good such as the color, the cleanliness, and the price. The CSI value obtained is 73,60 percent which is in satisfying category. According to the results of IPA attributes that should be top priorities are taste and texture of rice.Key words: Consumption, Customer Satisfaction, “Palas” rice